RELATIONSHIP BETWEEN ELECTRONIC MONEY AND GROWTH IN INDONESIA - Fitriyani; Hermawan, Rezky; Safitri, Nadia (RADJA PUBLIKA, 2023)
Money including electronic money has a very important role for growth, especially in revolution industry 4.0. era. The success of the digital payment system has supported the development of the financial and banking system. This study aims to analyze the relationship between e-money, M2, and economic growth in Indonesia from 2012 January to 2021 December. Granger causality test and Error Correction Model are used in this model to analyze the relationship between variables in this study. The results of the granger causality test shows that e-money and money have one-way relationship with growth. Furthermore, money shows a positive and significant effect on growth, while e-money does not have a significant effect. Coefficient of error term shows a negative and significant effect implies that the model in this study is converging to equilibrium and stable. Therefore, it is recommended for the government to increase the use of money including e-money to enhance the economy.